Perancangan Prototipe Sistem Bertenaga Mandiri Berbasis Pemanenan Energi Frekuensi Radio: Perancangan Prototipe Sistem Bertenaga Mandiri Berbasis Pemanenan Energi Frekuensi Radio - Edi Mulyana (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2025)
Electronic devices are generally powered by a power source such as an AC socket or a DC power source such as a battery. Batteries have a limited lifespan, so it is necessary to recharge the battery if the battery is rechargeable. In this paper we present a design for an independent power system where the power does not come from an AC voltage socket, but the power is obtained from the results of radio frequency energy harvesting. The selected frequency is the frequency for cellular that emitted from the Cell Phone Operator's Base Transfer System. The Radio Frequency Energy Harvesting system catch RF signal use monopole antenna receiver, then the RF signal converted into DC voltage (RF to DC converter) by a series of charge pump that also serves as amplifier which designed to 5-stage villiard multiplier. This system integrated by boost regulator to raise the level of voltage and regulate constant voltage. The voltage result from system is 300 mV at 100 m from BTS and 3,9 V at 30 cm from mobile phone. Another test with a LED indicator and suplying a power for charging process to battery AAA rechargeable Ni-MH. Keyword -cellular, energy harvesting, independent power system, monopole antenna, radio frequency